Perbedaan kematangan pemilihan karier antara siswa dan siswi kelas XII di SMKN 1 Cibinong - Suryaman, Neng Triyaningsih (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2018)
The research aimed to see difference in career selection maturity among XII grade’s male and female students. The type of research was quantitative along with comparative methods. The conclusion obtained that the career selection maturity between XII grade’s male and female students at SMK Negeri 1 Cibinong was not different significantly.The implication of this research is about the performance of career selection maturity test is valueable for students that have a high category in their career selection maturity for determining their career selection maturely, and shows that they have done their career development tasks optimally. Students with middle and low category in career selection maturity have impacts on their competention and attitude when choosing their career in the future.Although gender is one of the factor that influence a student’s career selection maturity, there is no difference that found in this research.